Parity and tanned white skin as novel predictors of vitamin D status in early pregnancy: a population‐based cohort study. (2nd July 2013) - Andersen, L. B.; Abrahamsen, B.; Dalgård, C.; Kyhl, H. B.; Beck‐Nielsen, S. S.; Frost‐Nielsen, M.; Jørgensen, J. S.; Barington, T.; Christesen, H. T.
Abstract Context In pregnancy, vitamin D insufficiency and deficiency, defined as serum 25‐hydroxyvitamin D (25(OH)D) <50 nM, and <25 nM, respectively, may have adverse effects for both mother and child. Prevalence estimates, and identification of subgroups at special risk, may be useful for the planning of preventive strategies. Objective To study the prevalence and risk factors of hypovitaminosis D in early pregnancy. Design and Methods In a cross‐sectional study of 1348 women in early pregnancy from the Odense Child Cohort, Denmark, 25(OH)D was determined and correlated to demographic and lifestyle variables (age, nationality, skin tone, parity, prepregnancy body mass index (BMI), smoking and sun exposure), using multiple linear and logistic regression analyses for all year, or stratified for summer and winter. The risk of vitamin D insufficiency was expressed as odds ratios (OR) with 95% confidence intervals in brackets. Results The prevalence of vitamin D insufficiency and deficiency was estimated to 27·8% and 3·5% respectively. In adjusted analyses, vitamin D insufficiency was directly associated with winter season, OR = 1·89 (1·35–2·63); increasing prepregnancy BMI, OR = 1·06 (1·03–1·10); and smoking, OR = 2·7 (1·34–5·41); but was less frequent in nulliparous, OR = 0·47 (0·33–0·68) and tanned Caucasians, OR = 0·63 (0·41–0·97). Season‐specific associations having parental origin from outside Europe in summer, OR = 4·13 (1·41–12·13); in winter smoking, OR = 3·15 (1·19–8·36); and prepregnancy BMI, OR = 1·12 (1·06–1·18). Conclusions Vitamin D insufficiency was widespread in early pregnancy. Associations to smoking, prepregnancy BMI and origin outside Europe varied with season. Multiparity and not being tanned in Caucasians represent new risk factors of vitamin D insufficiency.